Participatory forest management for improving livelihood assets and mitigating forest degradation: lesson drawn from the Central Rift Valley, Ethiopia - Girma, G.; Melka, Y.; Haileslassie, Amare; Mekuria, Wolde (Elsevier, 2023)
The study was conducted in Heban Arsi district, Central Rift Valley, Ethiopia to investigate the contribution of participatory forest management (PFM) to improving household’s livelihood assets and mitigating forest degradation. Data were gathered using household surveys, observation, key informant interviews and focus group discussions. During the entire study, 231 households (131 from PFM; 100 form non-PFM households), 35 key informants (25 from PFM; 10 from non-PFM) and 10 focus groups (6 from PFM; 4 from non-PFM) were involved. The livelihood assets framework was used to organize and analyze the quantitative data. The qualitative data was analyzed using topic coding and building categories, themes, and patterns of relationships. The introduction of PFM significantly (P < 0.05) improved the overall natural (index value of 0.72 and 0.58 for PFM and non-PFM, respectively), financial (0.73 and 0.61), physical (0.49 and 0.37), human (0.62 and 0.57) and social (0.77 and 0.59) livelihood asset values of local communities and contributed to the mitigation of forest degradation. On average, households involved in PFM displayed a 61.6%, 45.7%, 30.8% and 24.2% improvements in natural, financial, physical, and social assets, respectively. Households engaged in PFM showed a 37.4% improvement on the overall livelihood assets value, suggesting that PFM households displayed better livelihood assets compared to non-PFM households. However, the overall contribution of PFM to the livelihood assets showed skewed structure, suggesting that the improvements deviate from sustainability. The existing institutional structure including bylaws contributed a lot to strengthen PFM. Yet, it is crucial to strengthening the protection of forestlands through improving rule enforcement and commitments of both formal and informal institutions in managing forest resources. Also, sustaining the extraction of wood and non-wood forest products and the benefits from as well as integration of other interventions in PFM areas such as the provision of improved cook stoves and solar PV could help reduce forest degradation, improve the sense of ownership among local communities and sustain PFM activities. Further, expanding capacity building trainings and improving access to market could play a great role to sustainably manage forest resources through increasing the participation of local communities in decision making processes.